Developing Islamic Digital Storybooks to Foster Honesty Character in Early Childhood - Ahmad Syukron; Sri Watini; Ajat Ajat (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aimed to develop and evaluate the effectiveness of an Islamic digital storybook in fostering honesty character among early childhood learners aged 5–6 years. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The study involved 18 children from Group B at PG-TK Al Muslim Bekasi. Data were collected through observation, interviews, expert validation questionnaires, teacher response questionnaires, and documentation. The results showed that the developed media achieved a validity score of 88.30%, categorized as highly feasible. The practicality test also indicated that the media was highly practical for classroom implementation. Furthermore, the effectiveness test demonstrated a significant improvement in children’s honesty character, as reflected by the increase in pre-test and post-test scores and an N-Gain value of 0.65, categorized as moderate-to-high improvement. The findings indicate that the Islamic digital storybook is valid, practical, and effective in strengthening honesty character among early childhood learners. Therefore, this media can serve as an innovative Islamic-based digital learning resource for character education in early childhood settings.